Digital oscillography of proton-conductive polymer membranes - Prokhorov, Igor' Yur'evich (Электрохимическая энергетика, 2023)
Polyvinyl alcohol-based cast membranes have promising application in creating commonly available fuel cells and fuel synthesizers, as well as inexpensive water sources and microelectromechanical systems. In order to control the properties of such membranes a deep understanding of the charge transfer mechanisms and their relationship with the structure formed at a certain composition and manufacturing technology is required. A method for studying the structure of the proton-conductive polymer membranes using digital oscillography of ion currents excited by the low-frequency rectangular pulses with the amplitudes below the threshold voltage of the ionic conductivity in a dehydrated membrane, and for the analysis of the resulting ion current pulses (spikes) in the frames of the model of a proton pump acting in each layer of the membrane is proposed in this paper. Fast Fourier transform of these oscillograms reveals from 2 to 4 branches or spike sequences corresponding to the phases with different ionic conductivity and makes it possible to determine the thicknesses of both high-conductivity phase layers (7–30 µm) and low-conductivity phase interlayers (1–7 µm) formed in the process of polymerization. The reason of spike merging into bursts is described in terms of successively induced increase in the excited proton density over a threshold value in highly conductive layers. The resonance observed in dry proton membranes at the frequencies of about 2.2 to 3.0 kHz is interpreted as the burst merge point with the further increase in impedance due to proton lagging and respective decrease in the effective thickness of active layers. The effective charge carrier concentrations (as small as 1012 to 1013 cm−3) and the velocity (from 5 to 18 cm/s for the highly conductive phases which turned out to be much higher than those observed in solutions) are estimated. The asymmetry of the cast membranes, which becomes apparent at low frequencies and causes the generation of a direct ion current in response to excitation by a purely alternating current, is studied. It is found that the apparent conductivity determining contribution to the total ohmic resistance is made by a thin interlayer with a very low ion velocity, presumably surface layer, rather than the main layers. The conclusion on the optimization of the production technology and the composition of the proton membranes for various applications is made.